Experimental investigation of the far-field emission pattern of microdisk laser modes. (December 2020) - Kadinskaya, S A; Moiseev, E I; Kryzhanovskaya, N V; Zubov, F I; Mintairov, S A; Kalyuzhnyi, N A; Kulagina, M M; Fominykh, N A; Maximov, M V; Zhukov, A E
Abstract: We studied a far-field emission pattern for microlasers with InGaAs/GaAs quantum well-dots in the active region. Angular-resolved electroluminescence spectra measurement revealed various far-field patterns depending on current and resonance mode.